(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Immunity is the human body’s ability to resist toxins or organisms that cause damage to the tissues and organs, thereby demonstrating a defence mechanism for an improved quality of life. (Guyton and hall 2011)